What is the NCD service capacity and disruptions due to COVID-19? Results from the WHO non-communicable disease country capacity survey in the Americas region - Anselm Hennis; Silvana Luciani; Roberta Caixeta; Carolina Chavez; Dolores Ondarsuhu (BMJ Open)
Objective This article presents the Americas regional results of the WHO non-communicable diseases (NCDs) Country Capacity Survey from 2019 to 2021, on NCD service capacity and disruptions from the COVID-19 pandemic.Setting Information on public sector primary care services for NCDs, and related technical inputs from 35 countries in the Americas region are provided.Participants All Ministry of Health officials managing a national NCD programme, from a WHO Member State in the Americas region, were included throughout this study. Government health officials from countries that are not WHO Member States were excluded.Outcome measures The availability of evidence-based NCD guidelines, essential NCD medicines and basic technologies in primary care, cardiovascular disease risk stratification, cancer screening and palliative care services were measured in 2019, 2020 and 2021. NCD service interruptions, reassignments of NCD staff during the COVID-19 pandemic and mitigation strategies to reduce disruptions for NCD services were measured in 2020 and 2021.Results More than 50% of countries reported a lack of comprehensive package of NCD guidelines, essential medicines and related service inputs. Extensive disruptions in NCD services resulted from the pandemic, with only 12/35 countries (34%), reporting that outpatient NCD services were functioning normally. Ministry of Health staff were largely redirected to work on the COVID-19 response, either full time or partially, reducing the human resources available for NCD services. Six of 24 countries (25%) reported stock out of essential NCD medicines and/or diagnostics at health facilities which affected service continuity. Mitigation strategies to ensure continuity of care for people with NCDs were deployed in many countries and included triaging patients, telemedicine and teleconsultations, and electronic prescriptions and other novel prescribing practices.Conclusions The findings from this regional survey suggest significant and sustained disruptions, affecting all countries regardless of the country’s level of investments in healthcare or NCD burden.